Analisa Pengaruh Financial Distress Terhadap Harga Saham Dengan Model Altman Z-Score - Dora Ayu Utami; Desi Isnaini; Evan Stiawan (Jurnal Bisnis, Manajemen, dan Akuntansi, 2023)
This study aims to prove the effect of the ratio wcta, reta, ebita, mvebtl, sta and predictions of financial distress on stock prices at JII 70 for the 2019-2021 period. In this study, the type of research that will be used is quantitative research. The population of this study is all companies that have come out of the JII 70 calculations for 2019-2021, totaling 53 companies. The sample selection in this study used a purposive sampling method. The number of research samples is 34 companies. The types and sources of data used in this research are time series data and secondary data. The data were processed through the SPSS 16 program. The results showed that WCTA, RETA, EBITA, MVEBTL, STA X1) had a significant effect on stock prices. WCTA (X2) has a significant effect on stock prices. RETA (X3) has a significant effect on stock prices. EBITA (X4) has no significant effect on stock prices. MVEBTL (X5) has a significant effect on stock prices. STA (X6) has no significant effect on stock prices. WCTA, RETA, EBITA, MVEBTL, STA (X7) jointly affect the stock price of the JII 70 index for the 2019-2021 period by 11%, while the remaining 89% is influenced by other factors. Keywords: Financial Distress, Stock Price, Altman Z-Score, JII70